Worsening of heart failure by coronavirus disease 2019 is associated with high mortality. (26th January 2021) - Bocchi, Edimar Alcides; Lima, Ivna Girard Cunha Vieira; Biselli, Bruno; Salemi, Vera Maria Cury; Ferreira, Silvia Moreira Ayub; Chizzola, Paulo Roberto; Munhoz, Robinson Tadeu; Pessoa, Ranna Santos; Cardoso, Francisco Akira Malta; Bello, Mariana Vieira de Oliveira; Hajjar, Ludhmila Abrahão; Gomes, Brenno Rizerio
Abstract: Aims: Patients with advanced heart failure (HF) with reduced left ventricular ejection fraction (HFrEF) and concurrent coronavirus disease 2019 (COVID‐19) might have a higher risk of severe events. Methods and results: We retrospectively studied 16 patients with advanced HFrEF who developed COVID‐19 between 1 March and 29 May 2020. Follow‐up lasted until 30 September. Ten patients previously hospitalized with decompensated HFrEF were infected with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) during hospitalization. Six patients undergoing ambulatory care at initiation of COVID‐19 symptoms were hospitalized because of advanced HFrEF. All patients who experienced worsening of HFrEF due to COVID‐19 required higher doses or introduction of additional inotropic drugs or intra‐aortic balloon pump in the intensive care unit. The mean intravenous dobutamine dose before SARS‐CoV‐2 infection in previously hospitalized patients ( n = 10) and the median (inter‐quartile range) peak intravenous dobutamine dose during SARS‐CoV‐2 infection in all patients ( n = 16) were 2 (0–7) μg/kg/min and 20 (14–20) ( P < 0.001), respectively. During follow‐up, 56% underwent heart transplantation ( n = 2) or died ( n = 7). Four patients died during hospitalization from mixed shock consequent to severe acute respiratory syndrome with inflammatory storm syndrome associated with septic and cardiogenic shock during COVID‐19. After COVID‐19 recovery, two patients died from mixed septic and cardiogenic shock and one from sustained ventricular tachycardia and cardiogenic shock. Five patients were discharged from hospital to ambulatory care. Four were awaiting heart transplantation. Conclusion: Worsening of advanced HF by COVID‐19 is associated with high mortality. This report highlights the importance of preventing COVID‐19 in patients with advanced HF.